2020
DOI: 10.3389/fmars.2020.569936
|View full text |Cite
|
Sign up to set email alerts
|

Using Cost-Effective Surveys From Platforms of Opportunity to Assess Cetacean Occurrence Patterns for Marine Park Management in the Heart of the Coral Triangle

Abstract: Cost-Effective Surveys for Cetaceans here already help identify potentially important areas as well as highlight where to direct designated research efforts. We advise to protect currently unprotected cetacean important habitats, and strictly regulate human activities in the current use zones for future WNP rezoning processes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 101 publications
(114 reference statements)
0
5
1
Order By: Relevance
“…The NOAA-SWFSC surveys covered the entire Guatemalan oceanic zone where those species are typically found, while this study sampled only about a third of the same zone; thus, reducing the probability of encountering pelagic species. Also, some species are gregarious by nature and might be more difficult to spot and identify (Sahri et al, 2020). The total number of small cetacean species identified in this study was smaller than that reported for the neighboring country of Mexico (15 species; Rosales-Nanduca et al, 2011), and other countries of the eastern tropical Pacific including Costa Rica (12 species; May-Collado et al, 2005) and Colombia (12 species; Palacios et al, 2012).…”
Section: Cetacean Biodiversity Abundance and Spatial Distributioncontrasting
confidence: 57%
“…The NOAA-SWFSC surveys covered the entire Guatemalan oceanic zone where those species are typically found, while this study sampled only about a third of the same zone; thus, reducing the probability of encountering pelagic species. Also, some species are gregarious by nature and might be more difficult to spot and identify (Sahri et al, 2020). The total number of small cetacean species identified in this study was smaller than that reported for the neighboring country of Mexico (15 species; Rosales-Nanduca et al, 2011), and other countries of the eastern tropical Pacific including Costa Rica (12 species; May-Collado et al, 2005) and Colombia (12 species; Palacios et al, 2012).…”
Section: Cetacean Biodiversity Abundance and Spatial Distributioncontrasting
confidence: 57%
“…Bryde's whales have also been observed west of Lovina in the Buleleng waters of north Bali (Mustika, personal observation, currently listed as the Buleleng IMMA), indicating that the island Province of Bali may play an important role in the conservation of this species. Bryde's whales have also been observed in the Wakatobi National Park (Sahri et al, 2020; the Wakatobi IMMA), Raja Ampat in West Papua (Ender et al, 2014; candidate IMMA) and Savu Sea and Surrounding Areas IMMA (Marine Mammal Protected Areas Task Force, 2021c). The confirmed sightings of Bryde's whales in this study, and the likelihood that eight out of 19 unidentified baleen whales (Table 1) were also Bryde's whales, add to the postulation that the study area is an important feeding habitat and a possible breeding or nursing ground for this species.…”
Section: Lessons Learned From the Training (Objective 4) And Future Research And Actionsmentioning
confidence: 99%
“…Visual line‐transect surveys employed to observe cetaceans in the ocean are mainly conducted using ships and aircraft (Hammond et al, 2021). Buckland et al (2001) described line‐transect sampling method in detail; in brief, transect lines are placed randomly using a design in which each part of the study area has an equal probability of being surveyed (Sahri et al, 2020; Thomas et al, 2007). However, using ship and aerial surveys over relatively large areas can be prohibitively expensive (Sahri et al, 2020; Thomas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Buckland et al (2001) described line‐transect sampling method in detail; in brief, transect lines are placed randomly using a design in which each part of the study area has an equal probability of being surveyed (Sahri et al, 2020; Thomas et al, 2007). However, using ship and aerial surveys over relatively large areas can be prohibitively expensive (Sahri et al, 2020; Thomas et al, 2007). Furthermore, without the use of dedicated sighting survey vessels, it is difficult to cover large areas and increase the frequency of surveys using the transect sampling methods described by Buckland et al (2001).…”
Section: Introductionmentioning
confidence: 99%